PROFESSIONAL-METHODICAL PREPARATION OF THE FUTURE INFORMATIC TEACHER (World Bulletin of Social Sciences, 2023)
The article is based on the relevance of the problems of teaching computer science in educational institutions. There are also scientific conclusions and recommendations on the main directions for improving the methodological training of computer science teachers in the modern information and educational environment.
Keywords: innovative methods; pedagogical support; teacher's activity; modern teacher